2013
DOI: 10.1039/c3an00663h
|View full text |Cite
|
Sign up to set email alerts
|

In situ pH measurement during the formation of conversion coatings on an aluminum alloy (AA2024)

Abstract: The measurement of interfacial pH change is important for understanding the formation mechanism of conversion coatings that are used to protect metals from corrosion. In this work, we used a tungsten microelectrode to measure the interfacial pH change near the surface of an aluminium alloy (AA2024) during the formation of two conversion coatings: (i) a trivalent chromium pretreatment (TCP) and (ii) a Ti-based, non-chromium-containing coating. The tungsten microelectrode exhibited an open circuit potential (OCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 26 publications
4
91
0
Order By: Relevance
“…Zirconium was only detected in significant amounts above the S-phase particles after a treatment for 15 s. The greater thickness of the coating on the S-phase particles suggests an increased pH of the coating solution at these sites. 18 However, after a treatment for 120 s, zirconium was detected at the matrix and all second phase particles. The highest zirconium content was recorded at the S-phase particle, as also found at 15 s, while the amounts of zirconium at the matrix and at the θ and α particles were similar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconium was only detected in significant amounts above the S-phase particles after a treatment for 15 s. The greater thickness of the coating on the S-phase particles suggests an increased pH of the coating solution at these sites. 18 However, after a treatment for 120 s, zirconium was detected at the matrix and all second phase particles. The highest zirconium content was recorded at the S-phase particle, as also found at 15 s, while the amounts of zirconium at the matrix and at the θ and α particles were similar.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of alumina decreases significantly when the pH rises above about 4. 25 Li et al, using a microelectrode, observed that the pH at the coating surface increased from an initial value of 3.9 to 7.0 following a treatment of 120 s. 18 The pH then reduced to 4 after a treatment of 600 s. In the case of the present coatings, it is suggested that the initial rise in pH and rate of generation of Al 3+ ions resulted in a maximum thickness of hydrated alumina following a treatment of ∼60 s. Subsequently, the layer underwent a net thinning as the rate of formation reduced, since the coating growth limited the rate of diffusion of Al 3+ to the coating surface, and the rate of dissolution increased, due to decreases in the pH and possibly also the fluoride concentration at the coating surface. Since the process is sensitive to the surface pH, variations in thickness of the hydrated alumina layer across the surface of a specimen may be anticipated, owing to the difference in local cathodic activity.…”
mentioning
confidence: 99%
“…This is due to the enhanced cathodic reaction at the particles, which generates a locally increased pH that promotes the deposition of the Zr-and Cr-rich coating material. 7,20 Figures 6 displays transmission electron micrographs of crosssections of the coatings at locations on the aluminum surface remote from copper-rich particles after conversion treatment for (a-c) 120 s 3 (a, d) and solutions containing 0.05 g/L (b, e) and 0.5 g/L (c, f) copper sulfate. The crosssections reveal a chromium-and zirconium-rich outer layer above a thin aluminum-rich layer that contains oxygen and fluorine species.…”
Section: Resultsmentioning
confidence: 99%
“…The removal of the oxide layer exposes the metal surface where cathodic reactions take place. Oxygen reduction reaction, and possibly hydrogen discharge, which counterbalance aluminum oxidation, consume protons and causes a pH increase at the interface between the metallic substrate and the solution, as measured by Li et al 15 The high pH favors the precipitation of ions present in the solution, forming a hydrated layer of zirconium and chromium oxide. The thickness of the TCP layer is usually of the order of 100 nm, depending on the nature of the aluminum alloy, the concentration of the solution and the immersion time.…”
mentioning
confidence: 98%